Electrical and Thermal Anisotropy in Additively Manufactured AlSi10Mg and Fe-Si Samples - Martin Sarap; Hans Tiismus; Ants Kallaste; Mart Saarna; Märt Kolnes; Payam Shams Ghahfarokhi; Toomas Vaimann (Machines, 2024)
In the context of rising power densities in electrical machines, additive manufacturing presents an opportunity to develop more powerful thermal solutions. However, the physical properties of objects manufactured using this process remain unclear. This research examines the directional thermal and electrical conductivities of aluminum alloy (AlSi10Mg) and silicon steel (Fe-3.7%wt. Si) samples produced via laser powder bed fusion (LPBF), both prior to and following heat treatment. The findings indicate that the as-built aluminum samples exhibit higher conductivities in the orientation parallel to the LPBF build direction, while annealing results in higher conductivities overall and an absence of anisotropy. On the other hand, the silicon steel samples show constant conductivities and lack of anisotropy both before and after heat treatment. These results have practical applications in the design of additively manufactured electrical machines, where the thermal and electrical resistance of the materials have a major impact on thermal and electromagnetic performance.